2022
DOI: 10.1029/2021sw002944
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Solar Proton Events and Forbush Decreases on Ground‐Level Potential Gradient Recorded at Middle and Low Latitudes and Different Altitudes

Abstract: High‐energetic charged particles, such as solar protons, and phenomena such as Forbush decreases are eligible candidates to affect the global electric circuit. These effects have been studied by analyzing disturbances of the potential gradient in ground‐based measurements in fair weather regions. In this paper, we investigate deviations in the potential gradient diurnal curve, during solar proton events, and Forbush decreases, from the mean values obtained in fair weather conditions. In each situation, we sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Their amplitude A determined from AMS-02 measurements are 15.2% (4th), 19.4% (1st), and 14.2% (5th) respectively. These events were analyzed individually by Tacza et al (2022) and showed a significant PG increase during the FD. To see if these three events dominate the SEA analysis, we also remove these three events from our analysis to evaluate its impact on our results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their amplitude A determined from AMS-02 measurements are 15.2% (4th), 19.4% (1st), and 14.2% (5th) respectively. These events were analyzed individually by Tacza et al (2022) and showed a significant PG increase during the FD. To see if these three events dominate the SEA analysis, we also remove these three events from our analysis to evaluate its impact on our results.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, they have been speculated to be also able to affect the global electric circuit (GEC), and through which, affecting the weather patterns such as thunderstorms and lightnings on the Earth. Tacza et al (2022) performed SEA on 17 large SEP events and showed that at the 2.5σ level, there is a correlation between SEP flux increase and PG increase at fair weather conditions. Less clear is the effect of FDs on PG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations